Reception in a Family Health Unit: From the changes during the beginning of the experience with COVID-19 to the present day - Mendes , Amanda Caroline Oliveira Henriques; Lopes , Manuela Wanderley Ferreira; Correia, Maria da Conceição de Barros; Sousa , Válery Muniz de; Sousa , Micaela Maria de; Marques , Kátia Maria Gonçalves; Santos, Leonardo Cavalcanti Bezerra dos; Melo, Márcia Maria Dantas Cabral de; Nascimento, Zilma Ribeiro do; Lima, Niedje Siqueira de; Fontes, Luciana de Barros Correia (Seven Editora, 2023)
The objective of this experience report is to draw a comparison between the adjustments made in the Welcoming, in a Family Health Unit or FHU in the city of Recife, Pernambuco, from March 2020 to March 2023. The initial phase of this study comprised a descriptive and qualitative approach to the experiences, particularly directed to the welcoming of users. This one was from 37 professionals from the FHU of Vila União, in the city of Recife, State of Pernambuco. The professionals belonged to four Family Health teams. Considering the data obtained in the first half of 2021, the dynamics of welcoming were directed to screening, with little participation of the Oral Health team and problems related to dissatisfaction with the solution established for their problem. It was observed the need for adjustments in welcoming, with a view to a better level of satisfaction for both users and the care team. After an interval of two years or 24 months, it was found that there were few changes. The established organization remains with the Community Health Agent or CHA, triaging and referring users, with the Oral Health team being away from the reception and taking turns with another team. In this context, the current direction seems to reflect a recovery in the demand for care, not necessarily the quality of care. What has been found to be a problem is in a larger dimension, but is not discussed, at least until the month of March 2023. DOI:https://doi.org/10.56238/emerrelcovid19-035